Reproductive Biology Pleco (Pterygoplichthys pardalis Castelnau 1855) in Ciliwung River - Dewi Elfidasari; Farah Carolina Puspaningtias; Melta Rini Fahmi (Fakultas Keguruan dan Ilmu Pendidikan Universitas Labuhanbatu, 2022)
Pterygoplichthys pardalis is a type of fish that is widely used by people around the Ciliwung River as raw material for food production. In addition, P. pardalis has not been cultivated. The process of fish farming requires a number of information and data on fish such as reproductive biology. Therefore, the research aimed is calculating the reproductive aspects of P. pardalis. The result for this research can be applied for fish farmers to start P. pardalis bredding process. The methods used are P. pardalis sampling, measurement of total length and weight, dissection of samples, calculation of gonad weight and liver weight, egg diameter, fecundity, calculation of gonad maturity stages (GMS), gonadosomatic index (GSI), hepatosomatic index (HSI), relationship of fecundity with gonad weight, relationship of egg diameter with gonad weight, relationship of fecundity with total weight, and length-weight relationship. GMS calculation results showed most male fish found in GMS I, while females were most found in GMS IV. The smallest GSI value was found in GMS I and the highest was in GMS IV both in male and female and the fecundity was 737-3820 eggs with egg diameters ranging from 1.571 mm-4.310 mm. Both male and female P. pardalis have negative allometric growth patterns